Understanding the Learners' Study Process: A Vital Step Toward Better Learning - Genc, Zulfu; Tinmaz, Hasan (Elsevier Science Bv, 2013)
The learning, teaching and management are three crucial processes for instructional activities. As the current era moves toward student-centered instruction, the focus deeply shift to the students' learning processes. In that sense, more research studies must be performed on understanding how our students think or behave while they study. Therefore, this study aims to understand how the participants perceive their studying process. The study participants were the Computer Education and Instructional Technology (CEIT) students from a university in Turkey (n = 91; 40 male and 51 female). The study showed that 62 students are Deep Approach oriented learners whereas 29 of the students are Surface Approach oriented learners. It seems that one third of the study participants regrettably pay attention to the framework or key points of the subject matters without going deeper in their understanding. It seems that one third of the study participants regrettably pay attention to the framework or key points of the subject matters without going deeper in their understanding. (C) 2013 The Authors. Published by Elsevier Ltd.
2nd World Conference on Educational Technology Researches (WCETR) -- JUN 27-29, 2012 -- Near E Univ, Nicosia, CYPRUS
Keywords: Study process; deep approach learners; surface approach learners; learning; teaching